2019
DOI: 10.3390/md17120660
|View full text |Cite
|
Sign up to set email alerts
|

Fucoidan from Undaria pinnatifida Ameliorates Epidermal Barrier Disruption via Keratinocyte Differentiation and CaSR Level Regulation

Abstract: The epidermal barrier acts as a line of defense against external agents as well as helps to maintain body homeostasis. The calcium concentration gradient across the epidermal barrier is closely related to the proliferation and differentiation of keratinocytes (KCs), and the regulation of these two processes is the key to the repair of epidermal barrier disruption. In the present study, we found that fucoidan from Undaria pinnatifida (UPF) could promote the repair of epidermal barrier disruption in mice. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Fucoidans have been demonstrated to exert antiphotoaging effects against UV irradiation. We found that the fucoidan from UPF can ameliorate epidermal barrier disruption (25). In the present study, we explored the effect of UPF on UV-induced epidermis and dermis aging.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Fucoidans have been demonstrated to exert antiphotoaging effects against UV irradiation. We found that the fucoidan from UPF can ameliorate epidermal barrier disruption (25). In the present study, we explored the effect of UPF on UV-induced epidermis and dermis aging.…”
Section: Discussionmentioning
confidence: 91%
“…Fucoidan purified from Undaria pinnatifida (UPF) also exerts its photoprotective effect by augmenting the immune response and decreasing the matrix metalloproteinase-1 (MMP-1) level in UVB-irradiated mouse skin although its mechanism remains unknown (24). Based on results of our previous study (25), we hypothesized that UPF exerts antiphotoaging effects against UV irradiation. This study was aimed to explore the effect of UPF on UV-irradiated keratinocytes and fibroblasts and to explore the potential underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In mouse studies, which examined effects of CaSR knockdown (13,17,41), 90% knockdown of the CaSR protein in the epidermis eventually led to disruption of the epidermal permeability barrier. Treatment of immortalized keratinocytes with NPS‐2143 has also been reported to inhibit some measures of cellular differentiation (61). In this study, siRNA knockdown of CaSR in keratinocytes was only 60%.…”
Section: Discussionmentioning
confidence: 99%
“…11 Chen et al have demonstrated that fucoidan can regulate calcium levels in the body, thereby augmenting the sensitivity of keratinocytes to calcium ions, inducing keratinocyte differentiation under low calcium levels, and promoting epidermal barrier repair. 12 Moreover, studies have revealed that fucoidan mitigates lipid peroxidation, enhances antioxidant enzyme activity, suppresses the expression of inflammatory factors, and interacts with growth factors to promote dermal wound healing. 13,14 Recent research has suggested that fucoidan can regulate heparin-binding growth factors, such as FGF-2, to generate angiogenesis in vitro.…”
Section: Introductionmentioning
confidence: 99%